Collaborative Governance in the Bandung Basin Urban Area: A Case Study of Bandung Basin Urban Management Agency - Happy Pebruman Fadjaruddin Amalputra; Heru Nurasa; Benedictus Kombaitan; Sinta Ningrum (Jurnal Manajemen Pelayanan Publik, 2023)
Problems that arise in metropolitan areas are often cross-border in administrative boundaries across districts that require solutions involving coordination of several local governments, such as Bandung Basin Urban Area which consists of Bandung City, Cimahi City, Bandung Regency, West Bandung Regency, and Sumedang Regency. This study aims to examine the implementation of collaborative governance in development management in the Bandung Basin Urban Area. This research was conducted using qualitative methods and descriptive approaches, through analysis and processing of primary and secondary data. Primary data was collected through in-depth interviews with informants from the Bandung Basin Urban Area Management Agency. In previous research, it was found that the Greater Bandung Metropolitan area has already been in a collaborative governance scheme but still has many obstacles thus has not been able to encourage and facilitate cooperation within the relevant local government spheres. The latest research shows that there has been progress towards a better direction for collaborative governance in the context of the Bandung Basin Urban Area in general, even though the collaboration process has only been effectively started since September 2021. The analysis process focuses on the performance of the Bandung Basin Urban Area Management Agency's functions from the aspects of initial conditions, facilitative leadership, institutional design, and collaborative processes. The novelty in this study is directed at the proposed improvement of the collaborative governance model, in the scope of institutional aspects, knowledge and capacity development, collaboration processes, and aspects of authority.